2015
DOI: 10.1021/acs.iecr.5b00686
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Behavior and Anomalous Heat Evolution in Recombination of H2 and O2 on Pd-based Catalysts

Abstract: Gas flow-through microcalorimetry has been applied to study the Pd/Al2O3 type catalysts in the exothermic hydrogen recombination process: H2 + O2 → H2O, in view of the potential application in the passive autocatalytic recombination (PAR) technology. The flow mode experiments revealed thermokinetic oscillations, i.e., the oscillatory rate of heat evolution accompanying the process and the corresponding oscillations in the differential heat of process, in sync with oscillatory conversion of hydrogen. Mathematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In our laboratory, we have also observed the thermokinetic oscillations, i.e., oscillatory rate of heat evolution, in the H 2 oxidation on certain Pd/Al 2 O 3 catalysts. We discuss this phenomenon in a more systematic way in another article [47], in which we are reporting the thermokinetic oscillations in the hydrogen oxidation, including periods of mathematical chaos, as well as the accompanying thermal effects occasionally exceeding the heat of water formation by a factor of ca. three.…”
Section: Microcalorimetric Experimentsmentioning
confidence: 99%
“…In our laboratory, we have also observed the thermokinetic oscillations, i.e., oscillatory rate of heat evolution, in the H 2 oxidation on certain Pd/Al 2 O 3 catalysts. We discuss this phenomenon in a more systematic way in another article [47], in which we are reporting the thermokinetic oscillations in the hydrogen oxidation, including periods of mathematical chaos, as well as the accompanying thermal effects occasionally exceeding the heat of water formation by a factor of ca. three.…”
Section: Microcalorimetric Experimentsmentioning
confidence: 99%
“…In case of H 2 oxidation, self-sustained oscillations were observed on polycrystalline Pt and Pd wires, , polycrystalline Pt layers, or supported Pd and Rh catalysts , under atmospheric pressure conditions. Under high vacuum conditions, oscillations in H 2 oxidation have been observed only on well-ordered bimetallic Rh/Ni surface alloys and on sharp Rh nanotips under high electric field conditions (>10 V/nm) .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing importance of hydrogen-based energy generation in fuel cells 16 , much less attention has been given to (oscillating) catalytic H 2 oxidation. There are only few reports on oscillating H 2 oxidation on polycrystalline Pt and Pd wires 17 , 18 , polycrystalline Pt layers 19 , or supported Pd and Rh catalysts 20 , 21 under atmospheric pressure conditions. Under high vacuum conditions, enabling microscopic studies of H 2 oxidation, oscillations have been observed only on well-ordered bimetallic Rh/Ni surface alloys 22 and on sharp Rh nanotips under high electric fields (>10 V/nm; with the applied field causing the oscillations by stimulating the periodic formation of Rh surface oxide 23 ).…”
Section: Introductionmentioning
confidence: 99%